Wege zur Erreichung eines klimaneutralen Gebäudebestandes 2050. - Steinbach, Jan; Deurer, Jana; Senkpiel, Charlotte; Brandes, Julian; Heilig, Judith; Berneiser, Jessica; Kost, Christoph (My University, 2021)
Die Studie zeigt, welche Entwicklungen notwendig sind, um einen klimaneutralen Gebäudebestand bis 2050 zu erreichen. Dafür werden ein Trendszenario unter Berücksichtigung des aktuellen Rechts- und Förderrahmens sowie ein zielkompatibles Szenario (Zielszenario) unter der Prämisse einer Gesamtsystemoptimierung aller Sektoren entwickelt. Unter der Annahme eines verschärften Klimaziels werden im Zielszenario die energiebedingten CO2-Emissionen um 65% bis 2030 und um 100 % bis 2050 gegenüber 1990 reduziert.

The vision for a climate-neutral future by 2050 covers almost all sectors and is in line with the goals of the Paris Agreement. Climate neutrality is associated with a reduction in greenhouse gas emissions (GHG emissions) of 95 % compared to 1990 across all sectors. So far, there is no official definition of climate neutrality for the building sector. The existing target definition of a "nearly climate-neutral building stock" was defined by the Energy Efficiency Strategy for Buildings (ESG) in 2015 with the objective of an 80% reduction in non-renewable primary energy demand for the period 2008 to 2050 and was examined in scenarios. The sector target of the Climate Protection Plan 2050 for the year 2030, which is derived from the target definition of the ESG, envisages a reduction of greenhouse gas emissions of 67% by 2030 (compared to 1990). Due to the EU target of climate neutrality, a new target definition for the climate-neutral building stock is now also required, which is compatible with the reduction of 95% of total greenhouse gas emissions compared to 1990 and with the sector target for 2030 as it defined in the German Climate Change Act. Against this background, this project investigates which target gap exists by the year 2050 with regard to climate neutrality and with which cost-optimal trajectory a complete reduction of GHG emissions in the building sector can be achieved from an overall system perspective.
Keywords: Baubestand; Gebäudebestand; Energiebedarf; Emissionsminderung; Treibhausgas; Energieeffizienz; Klimaschutz; Kommunaler Klimaschutz; Szenario; Klimaneutralität